Hatchery Growth of Pure Strains and Intraspecific Hybrids of Juvenile Arctic Charr, Salvelinus alpinus (Canadian × Norwegian Charr) - March, B. G. E. de (Canadian Journal of Fisheries and Aquatic Sciences, 1991)
Growth parameters of 36 tank populations representing 23 full-sib families of Nauyuk and Norwegian Arctic charr (Salvelinus alpinus) and both reciprocal hybrids were determined for 1 yr. Hatching success of families was a maternal characteristic. Mean weights of families at 30 d after swim-up were related to maternal effects as well as the general and specific combining abilities of the two strains, with the weight contribution of the Nauyuk parent(s) larger than that of the Norwegian. At 125 d after swim-up, the mean weights and coefficients of variation (CVs) in the four types of crosses were Nauyuk dam × Nauyuk sire, 2.05 g ± 20%; Nauyuk dam × Norwegian sire, 2.10 g ± 24%; Norwegian dam × Nauyuk sire, 1.91 g ± 26%; and Norwegian dam × Norwegian sire, 1.71 g ± 31%. After 125 d, the Nauyuk dam × Norwegian sire families showed superior growth, while the Norwegian dam × Nauyuk sire families grew slowly and developed large size variation. At 325 d, reciprocal effects were evident, and mean weights and CVs were Nauyuk dam × Nauyuk sire, 36 g ± 45%; Nauyuk dam × Norwegian sire, 43 g ± 48%; Norwegian dam × Nauyuk sire, 30 g ± 68%; and Norwegian dam × Norwegian sire, 38 g ± 36%. The largest individual fish in the experiment were hybrids.